Venous thromboembolism prophylaxis after anterior cruciate ligament reconstruction: retrospective case-control study - Afana Hatem B.; Ashokan Shine; Nau Thomas (SICOT-J)
Introduction: Venous thromboembolism (VTE) is a rare but potentially serious complication following anterior cruciate ligament reconstruction (ACLR). There is no guideline for the routine use of anticoagulants post-ACLR surgery. Methods: This retrospective case-control study reviewed 199 patients who underwent ACLR between February 2020 and November 2024. Two groups were compared: Group A (n = 113) received no pharmacological prophylaxis, while Group B (n = 86) received low-molecular-weight heparin (LMWH) for 2 weeks postoperatively. The incidence of symptomatic VTE, postoperative bleeding, and related complications was evaluated. Results: No symptomatic VTE or bleeding complications were observed in either group. There was no statistically significant difference between the groups in terms of age, BMI, smoking, comorbidities, and postoperative weight bearing. There was a significant difference in surgical duration, graft type, and meniscal procedure. Discussion: Our findings support a risk-stratified approach rather than universal pharmacologic prophylaxis in ACLR patients.